Evaluation of indicators for improving the irrigation water use efficiency: Case of Guelma-Boucheggouf irrigated perimeter, Algeria - Kebieche, Abdelhak; Mouhouche, Brahim (Journal of Agriculture and Applied Biology, 2025)
This study contributes to the evaluation of irrigation performance in the irrigated perimeter of Guelma-Boucheggouf, located in the Wila-ya of Guelma in northeastern Algeria. The aim was to evaluate the irrigation water-use efficiency (WUEi) as a performance indicator of the irrigated system at the perimeter with regard to the existing distribution scheme. It is calculated according to the equation adopted within the framework of the Mediterranean Strategy for Sustainable Development “Plan Bleu” (MSSD) in 2008. It is the prod-uct of the overall efficiency of the supply-distribution network (E1) and the plot irrigation efficiency (E2), and is subject to the irrigation methods used. The calculations yielded irrigation water-use effi-ciency (WUEi) of 46.1%. Examining the results for the 2019 to 2022 irrigation campaigns revealed significant losses between the pumped volumes and the ones released, which indicates a low ad-duction efficiency (Ea) of 54.22% and explains the inadequacy of the release system compared with the water saving strategies adopted by the national water plan in Algeria. The results also reveal the im-portance of the existing distribution system reflected by a distribu-tion efficiency (Ed) of 82.08%, which reduced the overall efficiency of the network (E1) calculated from the two efficiencies to 56.58%, indicating an average loss of 9.8 Hm3 between the released volumes and those distributed. The plot efficiency (E2), calculated at 82%, was acceptable due to its dependence on the irrigation methods used; however further improvement is needed.